Analisis Kesalahan Berbahasa - Alfiati Alfiati (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
Language is an important tool in communicating with others. Through language, someone will be able to interact with each other. Thus, speaking human will be able to express his thoughts and feelings. Indonesia has a variety of ethnic groups so that in Indonesia there are various regional languages. When communicating between tribes the Indonesian people use Indonesian but when communicating in a family or tribal environment, they use local languages such as Javanese, Madurese, Sundanese, Balinese, and so on. This means that Indonesian people use two languages as communication tools or bilingual. It is because of the use of these two languages that there arises the existence of authority and interference.). Interference is the application of alternating use of two languages, causing language confusion. Thus, interference is a negative result of a bilingual. The use of language alternately results in language errors made by language users including spelling errors, sentence errors, and paragraph errors